(untitled) (Nigerian Journal of Technology, 2021)
Nigeria power system has been experiencing total or partial system failures in recent times and voltage instability is a strong factor. The paper seeks to perform the voltage stability analysis, based on static P-V plots, on buses located around and within the South-East zone of Nigeria. An injection group containing generators to serve as the source and a sink group as loads to be monitored are created. The generators are assumed to be within their min/max MW limits. The load is increased in the sink group as well as in the source group to maintain the same generation/load balance. Load power and bus voltages (P-V) curves are plotted on the load busbars and the first busbar to reach the voltage collapse and MW transfer limit are determined. From the results obtained, at a load of 100 MW, Makurdi bus recorded a voltage of 0.9301 pu which is already below the regulatory standards of ±5% of the nominal line voltage. It entered the region of instability at a load of 245 MW. This created a situation of system instability and a possible partial system collapse. Subsequently, at a load of 260 MW, the system clearly entered unstable region giving rise to partial system collapse of the network. http://dx.doi.org/10.4314/njt.v40i1.11